HUBUNGAN KONSEP DIRI DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA DI KECAMATAN MARO SEBO - Rafizul Rispaini; Akmal Sutja; Ninil Elfira; Muhammad Alridho Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the relationship between self-concept and premarital sexual behavior among adolescents in Maro Sebo District. The study employed a quantitative approach with a correlational design. The participants consisted of 48 adolescents selected through purposive sampling. Data were collected using closed-ended questionnaires to measure self-concept and premarital sexual behavior. Prior to hypothesis testing, the data were examined through normality and linearity tests as prerequisites for statistical analysis. The data were analyzed using the Pearson Product Moment correlation test. The results showed that the correlation coefficient between self-concept and premarital sexual behavior was r = –0.013 with a significance value of p = 0.931, indicating no significant relationship between the two variables. Although the negative correlation suggests that a more positive self-concept tends to be associated with lower premarital sexual behavior, the relationship was extremely weak and not statistically significant. These findings indicate that self-concept is not a dominant factor directly influencing premarital sexual behavior among adolescents. Therefore, premarital sexual behavior should be understood as a multidimensional phenomenon influenced by various internal and external factors. This study is expected to provide a reference for developing more comprehensive adolescent guidance and intervention programs involving families, schools, and the social environment.